How Tutors of Academic Writing Can Use the Theory of Transfer of Learning - Devet, Bonnie (Journal of Academic Writing, 2018)
One of the goals for tutors of academic writing is to help student writers tailor their writing processes to different writing projects so that students adapt what they know about one type of writing to another. This ability to write in different contexts can be explained by the theory of transfer of learning, which is generally defined as the ability to take something learned in one context and adapt, apply, or remix knowledge or skills in new contexts, including educational, civic, personal, or professional (Driscoll 2011). The mind, seeing similarities to what is already known, extends what is similar to another activity (Haskell 2001: 11). Tutors of writing need to know about transfer. Six categories of transfer – content, context, genres, writers’ prior knowledge, students’ ability to reflect, and dispositions – offer a lens to help researchers, trainers of tutors, or tutors (whether of L1 or L2 writers) to better identify where and how transfer could happen so that tutors are more prepared to look for opportunities to tutor for transfer. This paper offers insights into how these categories help tutors of academic writing who want to enhance students’ acquisition of academic skills.